The influence of e-government towards organizational performance in public sector - Husin, Rohana; Othman, Zakirah; Saad, Rohaizah (Akademia Baru, 2018)
e-Government is one of the management practices in order to improve the quality of service moreover public sector performance. This paper aimed to investigate the relationship between electronic government (e-Government), organizational information technology (IT) capability and public sector organizational performance. This study contributed to the literature in the area of IT in public sector. Past studies empirically examine relationships among the three variables which are widely practiced in private sector but receive less attention in the area of public sector. Four hypotheses had been developed aligned with the research framework. To test the research framework, the quantitative approaches using the survey method was used. A total of 149 questionnaires were distributed to Local Authority in Malaysia. Out of that, 87 questionnaires were usable for further analysis. Data were analyzed using descriptive statistics and inferential statistics approach. The result showed the organizational IT capability acts as a full mediator towards the relationship between e Government and organizational performance. The findings of this study are expected to contribute the increasing of knowledge in the area of government studies.